PENGARUH BEBAN KERJA PETUGAS AVSEC DALAM MELAKSANAKAN TUGAS KEAMANAN DAN PELAYANAN TERHADAP KETERTIBAN PENUMPANG DI SECURITY CHECK POINT BANDAR UDARA KALIMARAU BERAU - Annisa Cahyani; Anton Budiarto; Bambang Wasito (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Abstract Kalimarau Airport as one of the airports that became the gate of air transportation in Berau Regency. Still found passengers who have not implemented order as still found his goods that must be shared but still carried passengers up to Security Check Point (SCP) 2. This triggered the burden of Avsec officers. As a passenger checking center, Security Check Point needs special handling or attention. So it was concluded the need for a review related to the burden of Avsec officers at Security Check Point due to lack of orderly passengers. The research methodology uses descriptive research methods, namely by describing the current situation in the research object. The data is obtained from direct observation, library review, disscriptive and questionnaire deployment. The results of the research that have been carried out by the authors prove that using the validity test with the person correlation technique and the reliability test with the Cronbach's alpha formula and partial test, it is known that there is a significance that affects the Avsec workload on passenger order by 48.1%. So it can be seen that the workload variable has a significant effect on the order variable.